THE PROBLEM OF IMMUNITY: The Case of Sudanese President Al-Bashir - Petrović, Sonja (Pravni zapisi, 2013)
The responsibility of individuals who commit the most heinous crimes has been a pervading topic in political, legal and social discourse since the beginning of politically organised society. Where crimes committed are a consequence of organised government in a particular country, the question of responsibility becomes particularly difficult. This author considers the question of how one state, which is signatory to the Rome Statute should act when a president of a non-signatory country visits, and the ICC issues a warrant arrest for that individual. Should the state which is signatory to the Rome Statute act in accordance with its obligations under the Rome Statute or according to its bilateral obligations with non-signatory country? Through a comparative analysis of different solutions, the author searches for answers to these questions in order to provide a unique and harmonized  practice of national and international Courts. The author contends that the concept of international justice which will be established in the case of Al Bashir will be crucial for the future similar cases of contradictory international contracts, especially when one contract is  the Rome Statute.